”Lager på lager” : Att möjliggöra och synliggöra kommunikativa, kreativa och narrativa kompetenser - Svensson, Anette ; 0000-0002-6665-3990 (Forskning om undervisning och lärande, 2022)
In the study, a teaching design that focuses on stories in various forms of expression is applied in the first-grade classroom. The aim of the study is to examine teachers’ and pupils’ experiences of working with this teaching design in order to contribute with knowledge regarding how story-centred teaching can make possible and make visible pupils’ communicative, creative, and narrative competencies. In line with design-based research, an objective with the study is to bridge the gap between research and the educational practice, as well as to develop the educational practice. The results of the study show that working with a story through reception and production in various aesthetic and medial forms of expression make possible pupils’ communication, creative production, and deeper understanding of the story. Stories are strong resources for teaching and learning in the primary school classroom. Story-centred teaching can make possible and make visible pupils’ narrative competence, but in order for that to happen, there is a need for teaching that is flexible, particularly regarding time frames and directions.
Keywords: Litteraturdidaktik; estetiska uttrycksformer; kreativ literacy; kreativt skapande; lågstadiet; narrativ kompetens